Availability and use of primary care facilities in China: a nationwide representative survey. (October 2016) - Wong, William C W; Jiang, Sunfang; Ong, Jason; Peng, Minghui; Wan, Eric; Zhu, Zhanshu; Lam, Cindy L K; Kidd, Michael; Roland, Martin
Abstract: Background: China introduced a national policy to develop primary care in 2009, with 8669 community health centres (CHCs) established by 2014, employing more than 300 000 staff. However, against a background of the "barefoot doctor" legacy in rural China, mistrust of doctors, and over-reliance on specialist care, these facilities have been underused. This study aimed to evaluate the current quality of CHCs in China, including the organisation and infrastructure, as well as the use and training of the health-care professionals within primary care. Methods: We selected a random sample of 189 community health centres, stratified on the basis of geographical distribution and urban-suburban ratios, from throughout China between September and December, 2015. Two questionnaires, one for lead clinicians and another for primary care practitioners, covered the demographics of the clinic and clinical and training activities. Responses to the survey were obtained from 149 lead clinicians in community health centres and 3580 primary care practitioners (response rates 79% and 86%, respectively). Ethics committee approvals from a local board (HKU/HAW IRB: UW15-350) and the WHO Regional Office for the Western Pacific (2016.4.CHN.1.HSI) were obtained. Findings: Community health centres employed a median of eight doctors (IQR 4–14) and thirteen nurses (8–21) but only half of the doctors were registered as primary care practitioners (798 of 1734, 46%) and very few nurses had training specifically for primary care (92 of 1846, 5%). Most community health centres were in buildings previously designated as hospitals (86 of 149, 58%) and 87% (130) had inpatient beds. Although clinics were equipped with stethoscopes (146, 98%) and sphygmomanometers (145, 97%), only 83% (124) had otoscopes, 43% (64) had ophthalmoscopes, and 64% (95) had facilities for gynaecological examination. Clinical care was selectively skewed towards certain chronic diseases. Doctors saw a median of 12·5 (IQR 5·0–25·8) patients per day. Multivariate analysis showed that community health centres organised by private enterprises (β=11·1, 95% CI 1·3–20·8) and those which had pharmacists (1·9, 0·7–3·1) and nurses (0·32, 0·1–0·5) were associated with higher number of daily patients seen by doctor. Further, doctors saw fewer patients per day in clinics who opened 7 days a week (−3·8, 95% CI −7·2 to −0·3) and in those which provided a wider range of services (−3·3, −5·8 to −0·8). Interpretation: The survey shows that China has established a large, mostly young primary-care workforce and provided ongoing professional training. However, facilities are basic, with few clinics providing comprehensive primary care for a wide range of common physical and mental conditions. Use of community health centres by patients remains low. Funding: This project was supported by three funding sources: RGC seed fund for basic research, University Grant Council, HK SAR Government, entitled "Survey of the attitudes and needs of integrated HIV and STI services in community health centres in China (2015–16)" (project number 201411159004); Shanghai Key Discipline Construction Program in Public Health (Shanghai Municipal Commission of Health and Family Planning, project number 12GWZX1001); and Shanghai Excellent Academic Leaders Training Program in Public Health (Shanghai Municipal Commission of Health and Family Planning, project number GWDTR201210).